Acoustic monitoring of methane bubble plumes over the entire Southern Hydrate Ridge summit, 6-Jul-2018 to 8-Nov-2018 - Yann Marcon (PANGAEA, 2021)
This dataset contains a video file that shows the temporal and spatial variability of the methane bubble emissions over the Southern Hydrate Ridge summit. The bubble plumes were monitored with the SHR Overview Sonar, a rotating multibeam echosounder (OVRSRA101) connected to the underwater cabled observatory of the Ocean Observatories Initiative. The sonar had a bihourly sampling rate (every 2 hours) between 6 July and 8 November 2018. Latitude: 44.569969 Longitude: -125.147348 Elevation: -774.7 m Method: SHR Overview Sonar connected to the OOI underwater cabled observatory (instrument name given by OOI: OVRSRA101). Location: Southern Hydrate Ridge summit